Is Corporate Responsibility Converging? A Comparison of Corporate Responsibility Reporting in the USA, UK, Australia, and Germany - Chen, Stephen (Journal of business ethics, 2009)
Corporate social reporting, while not mandatory in most countries, has been adopted by many large companies around the world and there are now a variety of competing global standards for non-financial reporting, such as the Global Reporting Initiative and the UN Global Compact. However, while some companies (e.g., Henkel, BHP, Johnson and Johnson) have a long standing tradition in reporting non-financial information, other companies provide only limited information, or in some cases, no information at all. Previous studies have suggested that there are, country and industry-specific, differences in the extent of CSR reports (e.g., Kolk et al.: 2001, Business Strategy and the Environment 10, 15–28; Kolk: 2005, Management International Review 45, 145–166; Maignan and Ralston: 2002, Journal of International Business Studies 33(3), 497–514). However, findings are inconclusive or contradictory and it is often difficult to compare previous studies owing to the idiosyncratic methods used in each study (Graafland et al.: 2004, Journal of Business Ethics 53, 137–152). Furthermore, previous studies have relied mainly on simple measures, such as word counts and page counts of reports, to compare the extent of reporting that may not capture significant differences in the content of the reports. In this article, we seek to overcome some of these deficiencies by using textual analysis software and a more robust statistical method to more objectively and reliably compare the CSR reports of firms in different industries and countries. We examine a sample of leading companies in four countries (US, UK, Australia, and Germany) and test whether or not membership of the Global Compact makes a difference to CSR reporting and is overcoming industry and country specific factors that limit standardization. We conclude that GlobalCompact membership is having an effect only in certain areas of CSR reporting, related to the environment and workers, and that businesses from different countries vary significantly in the extent to which they promote CSR and the CSR issues that they choose to emphasize in their reports. These country differences are argued to be related to the different institutional arrangements in each country.